Czego nie będziemy wiedzieć o Czystej Formie? - Piotr Martin (Studia Philosophica Wratislaviensia)
In the article I attempt to specify the uniqueness of the key aesthetics categories. The argument is based on the concept of Pure Form put forward by Stanisław Ignacy Witkiewicz. I provide an argument for a claim that aesthetic terms categories must remain open, and I try to explain how to understand their openness. My attempt is based on my own interpretation of Pure Form as a concept belonging to aesthetic theory and associated not only with the creation of a work of art. I argue that the proposed interpretation may be accepted on the condition that we would never be able fully to understand how an object becomes a masterpiece. Pure Form has a dynamic, living, open, performative nature and thus will never be fully understood.